HUKUMAN HAD BAGI SESEORANG YANG MENYETUBUHI WANITA AJNABIAH MELALUI DUBUR PERSPEKTIF SYAFI’IAH - Alwin, Muhammad (IAIN Langsa, 2019)
This paper discusses the punishment for someone who has intercourse with an ajnabiah woman through the anal perspective of Shafi'iah. Imam Shafi'I himself did not give a direct opinion related to this issue. However, Shafi'i clerics address the problem, where the majority of Shafi'i clerics equate the intercourse done from the rectum with the intercourse done through the rectal female Ajnabiah. The method they use is the qiyas method, which according to them; both (adultery through qubul or rectum) produce lust and both are parts of the body that must be covered and guarded by a woman. Likewise, mandatory bathing for men who put their genitals in one of them (qubul and rectum).